Advocacy, Assessment and Accountability: Using Policy to Impact Practice in Ohio. Issue 3 (23rd March 2016) - Lorson, Kevin; Mitchell, Stephen
Abstract : Physical education teachers and programs are affected by increasing accountability demands. The purpose of this article is to explain Ohio's journey from advocacy for state physical education academic content standards to state-level policy that led to the development of state-wide assessments and data reporting on each school's report card. The process for developing the standards and assessments is shared, as well as teachers' perceptions of the effect of the assessments and accountability measures on physical education.